1957
DOI: 10.4141/cjas57-023
|View full text |Cite
|
Sign up to set email alerts
|

The Protein and Energy Requirements of Young Dairy Calves

Abstract: The protein and energy requirements of pre-weanling dairy calves were studied through the use of growth and balance trial techniques. Various levels of protein and energy were fed in both purified and semi-purified diets. The nitrogen retention of calves fed diets adequate in protein was 3.22 gm. per 100 gm. of gain in body weight. Energy requirement for maintenance was 44.7 digestible Calories per kg. of body weight per day and 268 digestible Calories were required per 100 gm. of gain in weight. These factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

1961
1961
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…This figure is intermediate between the values of 2-62 and 3-22 determined by Blaxter and Wood (1951b) and Brisson et al (1957) respectively, indicating that the nitrogen content of body weight gain does not differ between calves given concentrate diets and those given milk or milk replacement. This figure is intermediate between the values of 2-62 and 3-22 determined by Blaxter and Wood (1951b) and Brisson et al (1957) respectively, indicating that the nitrogen content of body weight gain does not differ between calves given concentrate diets and those given milk or milk replacement.…”
Section: Percentage Crude Protein In Dry Matter Of Dietcontrasting
confidence: 54%
See 1 more Smart Citation
“…This figure is intermediate between the values of 2-62 and 3-22 determined by Blaxter and Wood (1951b) and Brisson et al (1957) respectively, indicating that the nitrogen content of body weight gain does not differ between calves given concentrate diets and those given milk or milk replacement. This figure is intermediate between the values of 2-62 and 3-22 determined by Blaxter and Wood (1951b) and Brisson et al (1957) respectively, indicating that the nitrogen content of body weight gain does not differ between calves given concentrate diets and those given milk or milk replacement.…”
Section: Percentage Crude Protein In Dry Matter Of Dietcontrasting
confidence: 54%
“…RELIABLE estimates of the protein and energy requirements of milk fed calves have been obtained from the calorimetric and nitrogen balance studies carried out by Blaxter (1950), Blaxter and Wood (1951a, 1951b, 1952a, 1952b, Roy, Huffman and Reineke (1957), Cunningham and Brisson (1957), Brisson, Cunningham and Haskell (1957), Cunningham et al (1958), and Roy et al (1958). No such information is available for the ruminant calf which has been weaned from milk at an early age and fed subsequently on solid food.…”
Section: Rowett Research Institute Bucksburn Aberdeenmentioning
confidence: 99%
“…In each of three growth trials, Holstein male calves grew significantly faster (P < 0.05) when whole milk was supplemented with the energy sources glucose (cerelose) (Roy et al 1964), variation in dietary protein level at a relatively constant energy intake (Brisson et al 1957), or varying energy intakes up to levels found in whole milk at a constant protein intake (Mathieu and de Tugny 1965 During the first 10 days on treatment (the dietary adaptation period) there appeared to be a higher incidence of diarrhea on treatments 3-6 (4-l0Vo cerelose) than on treatments L and 2 (0 and2Vo cerelose) (Fig. 3).…”
mentioning
confidence: 99%
“…The ratio of crude protein to starch equivalent in the diet having 19-4% crude protein is 1:4 which is slightly wider than the value of 1:3-8 considered to be optimal in an earlier trial when groundnut meal was the protein source and when the gains were only half (454 g. daily) those recorded in the present experiment with fish meal. Since the requirement for protein relative to energy increases with increasing rate of gain (Blaxter and Wood, 1951;Brisson, Cunningham and Haskell, 1957) this affords further proof of the superior value of fish meal relative to groundnut meal in the general context of early weaning on high concentrate diets. SUMMARY 1.…”
Section: Discussionmentioning
confidence: 92%